Bio-energy conversion with carbon capture and utilization (BECCU): integrated biomass fermentation and chemo-catalytic CO2 hydrogenation for bioethanol and formic acid co-production. Issue 24 (3rd December 2021) - Guntermann, Nils; Mengers, Hendrik G.; Franciò, Giancarlo; Blank, Lars M.; Leitner, Walter
Abstract : Joining bio- and chemo-catalysis: whole-cell fermentation of glucose to ethanol is combined with in situ hydrogenation of the by-product CO2 to formic acid using a tailored Ru-catalyst in a water–tetradecane biphasic system. Abstract : We present an integrated process for in situ CO2 hydrogenation during bioethanol production by combining bio- and chemocatalysis. The biphasic catalytic system used comprises an aqueous whole-cell fermentation broth and a tailored organometallic catalyst in the organic phase. Glucose is converted to ethanol, and the by-product CO2 is simultaneously upgraded to formic acid in a single reactor unit. Under the optimized conditions, 26% of the generated CO2 was hydrogenated directly.